A 3D Slab-Based Methodology to predict end of life for concrete pavements. Issue 14 (6th December 2022) - Geary, Georgene M.; Tsai, Yichang (James)
ABSTRACT: Observation of fatigue cracking in concrete pavement slabs can be an indication that the life of the pavement is coming to an end. Alternatively, cracked slabs can be due to uneven foundation support and just an isolated occurrence. The resulting action and cost for these two conditions are vastly different. What if there was a way to predict when a pavement's life could be extended using concrete pavement restoration compared to when it was necessary to reconstruct? This paper provides a novel way, using a 3D Slab Based Methodology to characterise cracking in jointed plain concrete slabs and combines this with Remaining Service Life and hazard rate based on Weibull reliability theory to provide that answer for conventional concrete pavements. Using examples of several different pavements a comparison of this method to the traditional percent cracking is made. The results show that the new method, incorporating the impending failure concept, enables researchers and transportation agencies to identify the end of a concrete pavement's life better than percent cracking by taking full advantage of 3D pavement surface data.